Malnutrition in all its forms and socioeconomic status in Bolivia. (11th August 2020) - Miranda, M; Bento, A; Aguilar, AM
Abstract: Objective: To estimate the prevalence of malnutrition (undernutrition and excess BMI) among children under the age of 5 years and women of reproductive age in Bolivia considering three socioeconomic indicators: wealth, education and ethnicity. Design: We used the 2008 nationally representative Bolivian Demographic and Health Survey (DHS). Malnutrition's prevalence was estimated by wealth, ethnicity and educational level. Wealth index was measured based on the DHS methodology and nutritional status by using WHO standards and indicators. Education level (EL) was categorized by years of formal education. Setting: Bolivia. Participants: In total, 5·903 children <5 years, 3·345 adolescent women (15–19 years) and 12·297 women (20–49 years) with available information on anthropometric measurements· Results: A disproportionate prevalence of malnutrition was observed among different wealth groups: lower wealth tertiles show the higher prevalence of stunting (>30 %) and anaemia (>40 %) in all ages· The prevalence of overweight and obesity tends to rise with age from childhood (10·02–11·60) to adolescence (27·9–31·03), reaching highest levels in women of reproductive age (56·02–57·76). According to wealth tertiles, higher prevalence of overweight and obesity was found in children of high tertile (12·23), adolescent women of low (32·56) and adult women of medium tertile (63·08). Conclusions: The present study shows that currently Bolivia is in a transitional stage, faces not only the problem of undernutrition but also those of overnutrition, showing strong inequalities according to socioeconomic and education status. This study calls for state-specific policies keeping in view of the nature of inequality in malnutrition in the country and its differential characteristics across wealth status.